(untitled) (International Journal of Innovative Technologies in Economy, 2021)
Can hardly be overestimated the importance of the road construction industry for the economic development of any country. According to the Kyiv School of Economics (KSE) the implementation of the infrastructure program "Great Construction", a large share of which correspond to projects in the road sector, in the long-term effects will increase GDP in the next 5 years by 2,2% [ 1]. In this context it is necessary to effectively use financial resources intended for rehabilitation of the transport and operational characteristics of Ukrainian road network To accomplish this it is extremely important to objectively determine the cost of road works on the early stages of the investment process, which can be achieved by using the relevant and authentic data on the cost of all components. The operating cost of road construction equipment is one of the most significant factors affecting the cost of work and increasing the profitability of enterprises. For reliable determination of the operating cost of road construction equipment at the stage of preparation of investor budget documentation it is necessary to use Average operating cost of road machinery and mechanisms recommended by Ukravtodor (hereinafter – UPVEM). The UPVEM provide the average actual operating operation of road equipment. The objectivity of calculations is ensured by an up-to-date regulatory framework, systematic updating of the labor cost and cost of material resources and obtaining information on the actual costs of contractors. When calculating the pricing documentation the cost of road machines and mechanisms is calculated on the basis of the Average operating cost of road machinery and mechanisms. The Average operating cost are calculated by averaging the cost component data received from road market participants. Therethrough, the enterprises that have actual costs which exceeding the Average operating cost losing a competitive advantage and receive a deterioration in the economic efficiency of their activities due to overspending on the operation of machines.